Hubungan Durasi Bermain Game Online Dengan Resiko Terjadinya Neck Pain Pada Generasi Milenial Di Perumahan Magersari Indah Mojokerto - Sri Lestari Wati; Agung Hadi Endaryanto; Sartoyo Sartoyo; Wahyu Teja Kusuma (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Neck discomfort has a numberof causes, including bad posture and mechanical strain. Sensitization of free nerve terminals in muscles can cause muscle discomfort. Muscle pain is caused by both chemical and mechanical mechanisms, because free nerve terminals function as mechanonociceptive and chemonociceptive reseptors. Methods: This research has 20 respondents using purposive sampling. The research design uses a pre-experimental kuantitatif and eksperimental approach.Results: There was a correlation between the duration of playing online game and the risk neck pain of the millenial generation at Perumahan Magersari Indah Mojokertoin 2022 with spearman’s rho 0,000 < α (α = 0,05) significance and correlation coefficient 1,000 > 0,444 value.Conclusion: The duration of online game player respondents at Perumahan Magersari Indah Mojokerto based on The Grapic Visualization & Usability Center, The georgia Institut of Technology is in the medium category with a value.